The importance newspaper sources for the study of typography and graphic arts: the case of poblano journal el aprendiz de tipografía (1896) (2013)
In recent decades, studies on the graphic arts of thenineteenth century were made by analyzing the role ofperiodicals in the political and cultural development ofLatin America. However, the use of such works as primarysource of typographic production of that period has beenless addressed. In this essay, El Aprendiz de Tipografía, abiweekly Pueblano newspaper is analyzed in order to letsus know the contents, visual structure and operation of aprinting shop in the late nineteenth century.